Problems and Key Factors of CRM Implementation - Lendel, Viliam (Communications - Scientific letters of the University of Zilina, 2009)
CRM value chain identifies five key steps in the development and implementation of a CRM strategy: customer portfolio analysis, customer intimacy, network development, value proposition development, and manage customer life cycle. These five primary stages of the CRM value chain represent three main sequential phases of CRM strategy: analysis, resource development and implementation. This article deals with CRM value chain and diagnostics of the level of Slovak companies in the CRM area.